Carbon intercalated MoS2 cocatalyst on g-C3N4 photo-absorber for enhanced photocatalytic H2 evolution under the simulated solar light. (30th April 2023) - Wei, Xuegang; Zhang, Xiaqing; Ali, Salamat; Wang, Jiatai; Zhou, Yongjie; Chen, Hao; Zhang, Guangan; Qi, Jing; He, Deyan
Abstract: Despite MoS2 being a promising non-precious-metal cocatalyst, poor electronic conductivity and low activity for hydrogen evolution caused by serious agglomeration have been identified as critical roadblocks to further developing MoS2 cocatalyst for photocatalytic water splitting using solar energy. In this work, the density functional theory calculations reveal that carbon intercalated MoS2 (C-MoS2 ) has excellent electronic transport properties and could effectively improve catalytic activity. The experiment results show that the prepared tremella-like C-MoS2 nanoparticles have large interlayer spacing along the c-axis direction and high dispersion because of intercalation of the carbon between adjacent MoS2 layers. Furthermore, the heterostructure photocatalyst of C-MoS2 @g-C3 N4 formed by loading the cocatalyst of C-MoS2 onto g-C3 N4 nanosheets exhibits the H2 evolution rate of 157.14 μmolg −1 h −1 when containing 5 wt% C-MoS2 . The high photocatalytic H2 production activity of the 5 wt% C-MoS2 @g-C3 N4 can be attributed to the intercalated conductive carbon layers in MoS2, which leads to efficient charge separation and transfer as well as increased activities of the edge S atoms for H2 evolution. We believe that the C-MoS2 will offer great potential as a photocatalytic H2 evolution reaction cocatalyst with high efficiency and low cost. Graphical abstract: Image 1 Highlights: The intercalation of carbon between adjacent MoS2 layers efficiently promotes electronic conductivity of MoS2 cocatalyst. The intercalation of carbon layers is beneficial to improving the activity of the edge S atoms. The intercalated carbon layers effectively prevents the stacking of atomic layers (S–Mo–S). The 5 wt% C-MoS2 @g-C3 N4 exhibits remarkable photocurrent responses and efficient H2 evolution performance.